2009
DOI: 10.1519/jsc.0b013e318192b7c1
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Influence of Two Intensities of Aerobic Exercise on Strength Training Performance in Elderly Women

Abstract: The aim of this study was to compare the acute influence of 2 intensities of aerobic exercise on a strength training session in physically active elderly women. Twenty-five women (74.3 +/- 2.8 years) with previous experience in both resistance and aerobic exercise volunteered to perform aerobic activity (60 and 80% maximum heart rate) followed by a training session on leg press, leg extension, and leg curl exercises. After aerobic intensity training, the number of repetitions in each set was analyzed to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
2
9
0
2
Order By: Relevance
“…Similar reductions in isokinetic peak torque (1) and leg press performance (46) have been reported following long slow distance (36-150 minutes) and interval cycle ergometry. In elderly women, larger reductions in repetition number were seen following a high-intensity (80% of HRmax) versus a moderate-intensity (60% of HRmax) treadmill protocol (26). During 9 weeks of concurrent training, similar lower-body strength attenuation has been reported between walking uphill and cycling (20-40 minutes) before RE (16).…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Similar reductions in isokinetic peak torque (1) and leg press performance (46) have been reported following long slow distance (36-150 minutes) and interval cycle ergometry. In elderly women, larger reductions in repetition number were seen following a high-intensity (80% of HRmax) versus a moderate-intensity (60% of HRmax) treadmill protocol (26). During 9 weeks of concurrent training, similar lower-body strength attenuation has been reported between walking uphill and cycling (20-40 minutes) before RE (16).…”
Section: Discussionmentioning
confidence: 65%
“…When RE followed an AE protocol (P1-P4), subjects were given a 10-minute rest interval. Although previous studies have shown muscle performance may be compromised 2 minutes to 8 hours following AE (1,26,27,46), a 10-minute rest period was selected because it more realistically represents the amount of time taken between modalities in practical settings and has been studied previously (13). During this time, subjects spent 2 minutes on the treadmill cooling down from the AE protocol and performed 3 light sets of RE (1 set each of the high pull, squat, and bench press with 30-50% of 1RM for 5-10 repetitions per set) in preparation for the protocol which promptly began 10 minutes after completion of the AE protocol.…”
Section: Resistance Exercise Protocolsmentioning
confidence: 93%
See 2 more Smart Citations
“…Após 48 horas de intervalo, foi feito um re-teste para avaliar a reprodutibilidade das cargas em 10RM. Os resultados mostraram-se semelhantes aos achados de Lemos et al 15 , com r >0,9 para os dois exercícios (cadeira extensora e mesa flexora). Para a realização dos testes de 10RM, os voluntários foram divididos em dois grupos aleatoriamente.…”
Section: Procedimento De Coletaunclassified